Meiofauna, microflora and geochemical properties of the late quaternary (Holocene) core sediments in the Gulf of Izmir (Eastern Aegean Sea, Turkey) - Yumun, Zeki U.; Meric, Engin; Avsar, Niyazi; Nazik, Atike; Barut, Ipek F.; Yokes, Baki; Sagular, Enis K.; Yildiz, Aysegul; Eryilmaz, Mustafa; Kam, Erol; Bassari, Asiye; Sonuvar, Bora; et al. (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
The Gulf of Izmir has seen the construction of marinas at four locations; Karsiyaka, Bayrakli, inciralti and Urla (Cesmealti). Six drilling holes have been structured for each location. Morphological abnormities observed in foraminifer tests, obtained from these core drillings, and coloring encountered in both foraminifer tests and ostracod carapeces, provide evidence of natural and unnatural environmental pollution. The objectives of this study are to identify micro and macro fauna, foraminifers in particular, contained within sediments in the above-mentioned locations; to investigate the background of pollution in the Gulf Region; and to determine pollution's impact upon benthic foraminifer and ostracods. Cesmealti foraminifera tests did not lead to color and morphological changes. But foraminifera tests samples collected from Karsiyaka, Bayrakli and Inciralti led them to turn black (Plate 4-6). However, concentrations of heavy metals (Ni, Cr and Mn) obtained from the sediments of Karsiyaka, Bayrakli and Inciralti locations are higher than those obtained from the cesmealti samples and high concentrations of these elements may be the cause of the color change in the samples during the foraminifera tests. In Karsiyaka and Bayrakli ostracod samples, Bosquetina carinella, Pterygocythereis jonesi, Semicytherura species; in the Cesmealti/Urla zone, Cyprideis torosa; in Inciralti, Pseudopsammocythere reniformis; and in four zones, Loxoconcha and Xestoleberis species were observed in the range of relative frequency. The same analyses were done on nannoplankton but they did not lead to color and morphological changes. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Meiofauna; Microflora; Geochemical analysis; Quaternary sediments; Gulf of Izmir; Turkey; METALS; Geology